Kearifan Lokal Budaya Masyarakat Bugis dalam Tradisi Mattampung Di Desa Sumberjaya Kabupaten Banyuasin (Suatu Kajian Semiotik) - Besse Mardianti; Missriani Missriani; Muhammad Ali (Jurnal Ilmiah Dikdaya, 2023)
The mattampung tradition is a tradition of changing tombstones, this tradition has existed from the ancestors as a form of family responsibility in order to get the best place with Allah SWT. This study aims to (1) describe a sign and meaning contained in the mattampung tradition of the Bugis community in Sumberjaya Village, Banyuasin Regency in Peirce's semiotic study (2) describe the local wisdom values of the culture of the Bugis community in Sumberjaya Village, Banyuasin Regency. The method in this research is to use qualitative research with descriptive methods. The data in this study is information obtained through direct research results from informants. The data sources in this study were people who were seen as having knowledge of the mattampung tradition. Data collection techniques in this study used observation techniques, interview techniques, and documentation techniques. The results in the study show that the results of the signs used in this mattampung tradition include: 7 kinds of cakes; cows, wall of graves, barazanji, mappasili, manisa/tombstones, leppek-leppek and bananas, side dishes, and puluk. Local wisdom values in the mattampung tradition include: compromise values, religious values, historical values, shared values, mutual cooperation values, deliberation values, and tolerance values